Impact of photovoltaic systems integration on electricity distribution networks - Esmaeel Ibraheem, Wadhah (2014)
Traditionally, power systems are designed to operate in a unidirectional power flow. In the past few years, integration of solar photovoltaic (PV) systems on distribution network has grown rapidly given its potential technical and economic benefits, which include higher network utilization, enhanced reliability and loss reduction. However, the high PV generation during low demand periods may cause potential network problems. In addition, PV generation depends directly to the sun irradiance which could potentially cause problems in the cases of high PV penetration level. The intermittency of the power generated from the PV plants may introduce voltage fluctuation and power quality issues. These issues may limit the PV penetration level and hence necessary measures are needed to alleviate the potential problems. This dissertation investigates the steady state impact of the PV plant penetration on the operation of power distribution networks. This includes the impact of PV generation of the network losses. In addition, the light and heavy load cases have been considered in this work to analyze their respective impact on the network voltage. The maximum PV penetration level that can be injected into the grid is identified. Mitigation strategy has also been proposed to control the voltage fluctuation that caused by PV plants. Standard IEEE distribution test cases have been modeled by utilizing OpenDss simulator. These test cases were used to perform the case studies of distribution systems in order to evaluate the impact of grid connected PV systems. The results indicate that the integration can have a positive impact and negative impact on the connected grids. The interest lies in the voltage improvement at load buses and the reduction in the system losses. The maximum capacity and the impact of the PV on the grid connected system depend on the PV size, installation location and system topology. The results also show that the STATCOM technique can effectively reduce the voltage fluctuation in the network.